Analisis Perkembangan E-Business di Era Gen Z - Vina Natalia (Jurnal Ekonomi dan Bisnis Digital, 2025)
The development of e-business in the digital era has significantly impacted economic patterns, particularly for Generation Z in Indonesia. This generation, raised with technology and the internet, excels in utilizing digital platforms for economic activities, both as consumers and entrepreneurs. This study employs a descriptive qualitative method to analyze the role of Generation Z in the digital economy, focusing on e-commerce trends and the challenges faced. The findings reveal that Generation Z plays a crucial role in the growth of the digital economy through high consumption on e-commerce platforms, an increasing number of young entrepreneurs, and their involvement as digital content creators supporting online marketing. However, challenges such as limited digital literacy and internet access in certain areas remain obstacles that need to be addressed. Therefore, strategies involving the government, private sector, and society are necessary to enhance digital literacy and expand technological infrastructure to support an inclusive and sustainable digital economy.